Investigation of Maximum Distance Reach for Spectrally Efficient WDM System with Mixed Data Rates and Signal Formats - Bobrovs, Vjaceslavs; Udalcovs, Aleksejs; Trifonovs, Ilja; Celmins, Talis (Elektronika ir Elektrotechnika, 2013)
The authors have investigated the maximum distance reach for wavelength division multiplexed (WDM) fiber optic transmission system (FOTS) where optical signals are transmitted with two different bitrate per channel (i.e. 10 and 40 Gbit/s) and for optical signal modulation three different modulation formats are used: NRZ-OOK, 2-POLSK and NRZ-DPSK. These chosen modulation formats encode information by manipulating with the different optical signal freedom degrees: amplitude, phase and state of polarization. The system’s maximum distance reach was detected for the most spectrally efficient WDM system’s configuration: [1st, 4th and 7th channels: NRZ-OOK, R= 10 Gbit/s] – [2nd, 5th and 8th channels: 2-POLSK, R=40 Gbit/s] – [3rd, 6th and 9th channels: NRZ-DPSK, R=40 Gbit/s]. It was done using iteration loops that consisted from chromatic dispersion compensation module, optical signal amplifier and one span of standard single mode fiber. One iteration loop corresponding to such configuration emulates one sector of fiber optic transmission line. It is found that the maximum distance reach depends on investigated system’s average spectral efficiency and the length of SSMF span. DOI: http://dx.doi.org/10.5755/j01.eee.19.1.1120